2009
DOI: 10.1017/s003118200999165x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and regulation ofTrypanosoma bruceiVSG-specific antibody responses

Abstract: The review addresses how infection with Trypanosoma brucei affects the development, survival and functions of B lymphocytes in mice. It discusses (1) the contributions of antibodies to trypanosome clearance from the bloodstream, (2) how B lymphocytes, the precursors of antibody producing plasma cells, interact with membrane form variable surface glycoprotein (VSG), i.e. with monovalent antigen that is free to diffuse within the lipid bilayer of the trypanosome plasma membrane and consequently can cross-link B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…This is a mechanism of organized surface coat switching that allows these extracellular parasites to continuously escape the host adaptive immune system (12). However, recent data suggest that trypanosomes also actively undermine the adaptive response by causing rapid depletion of the B‐cell compartment (13,14).…”
Section: Mouse Models As a Tool To Study The Humoral Responses Againsmentioning
confidence: 99%
“…This is a mechanism of organized surface coat switching that allows these extracellular parasites to continuously escape the host adaptive immune system (12). However, recent data suggest that trypanosomes also actively undermine the adaptive response by causing rapid depletion of the B‐cell compartment (13,14).…”
Section: Mouse Models As a Tool To Study The Humoral Responses Againsmentioning
confidence: 99%
“…Indeed, it has been estimated that the VSG density of intact T. brucei parasites is 20 times higher than the density required for BCR cross-linking. So, even if a VSG mosaic coat consists out of two antigenically district variants, each of the variants should in theory be able to mediate regular B cell activation, which is apparently not what happens (60). Yet, experimental infections in distinct mouse strains, as well as their F1 offspring, have shown that susceptibility to infection in terms of limited parasitemia control and shortened survival can be linked to the impaired capacity to mount a proper anti-VSG response.…”
Section: Trypanosomes Avoid Antibody-mediated Killing By Dynamic Surfmentioning
confidence: 99%
“…False-positive results have been reported in areas of low endemicity [26], and in several foci in West Africa were found some T.b. gambiense strains lacking the gene that encodes the surface glycoprotein LiTat 1.3 [27], main gene targeted by the agglutination process [28, 29]. To solve this problem, in addition to CATT are performed microscopic examinations of lymph aspirated from enlarged cervical lymph nodes or of blood films to assess the presence of the parasite in the lymph or blood [30].…”
Section: Diagnosismentioning
confidence: 99%
“…The emerging challenges for the development of a vaccine against African trypanosomiasis were recently reviewed [29, 110], and in this section, they will be briefly discussed. The cell surface of the procyclic and epimastigote forms of T.b.…”
Section: Treatment and Vaccine Developmentmentioning
confidence: 99%